DEVELOPMENT OF ELEMENTS OF TECHNOLOGY FOR PLANTING MATERIAL OF LETTUCE (LACTUCA SATIVA L.) ON VIRUS-FREE BASIS USING METHODS OF BIOTECHNOLOGY - O. B. Romanova; A. V. Soldatenko; O. A. Chichvarina; V. A. Akhramenko; O. V. Pavlova; V. S. Romanov (Овощи России, 2019)
The article presents the results of research on the production in vitro of regenerated plants from the seeds of cultivars of lettuce (Lactuca sativa L.) Emerald, Bouquet, Chameleon (FSBSI Federal Scientific Vegetable Center), susceptible of aspermia tomato (Tomato aspermy cucumovirus) – AsTV. Seeds of strongly susceptible to AsTV varieties of salad Chameleon and Bouquet were subjected to thermotherapy at different temperatures (37°C, 38°C, 40°C) for a different time interval (1, 3, 5, 7, 10 days) in dry form and when moistened. Marked varietal specificity during germination of seeds after thermotherapy. Thus, the greatest number of seedlings in the emerald variety was obtained after 5 days of thermotherapy (10.0±0), while the Bouquet variety had the best results after 3 days of thermotherapy (9.3±1.2) with moisture. After thermotherapy of dry seeds by 40°C plant material of cultivar Emerald was planted on solid and liquid culture media. The conditions of step sterilization of lettuce seeds for introduction into the culture in vitro were chosen: washing in 96% ethanol, then in 50% aqueous solution of "Whiteness" with the addition of Twin-20, after in sterile distilled water. The nutrient medium for germination of lettuce seeds was used: Gamborg B5 (2% sucrose, 7.0 g/l agar), and the liquid nutrient medium was of that composition. The obtained seedlings were cutted and transferred to medium MS (2% sucrose, 0.1 mg/l ha and 1 mg/l BAP, 3.0 g/l phytogel). The formed shoots for rooting were transferred to the MS medium (2% sucrose, 3.0 g/l phytogel). In the future, lettuce plants will be adapted in vivo and tested for the presence of tomato aspermia virus in the planting material.